To Wrap Or to Not Wrap Cucumbers? - Shrivastava, Chandrima; Crenna, Eleonora; Schudel, Seraina; Shoji, Kanaha; Onwude, Daniel; Hischier, Roland; Defraeye, Thijs (Frontiers in Sustainable Food Systems, 2022)
In light of increasing public pressure, retailers strive to remove plastic packaging as much as possible from fresh fruits and vegetables to reduce the environmental impacts along their supply chains. Plastic packaging, however, also has an important protective function, similar to the fruit's peel. For cucumbers transported from Spain and sold in Switzerland, our investigations in the form of a life cycle assessment study showed that the plastic wrapping has a rather low environmental impact (only about 1%) in comparison to the total environmental impacts of the fruit from grower to grocer. Hence, each cucumber that has to be thrown away has the equivalent environmental impact of 93 plastic cucumber wraps. We found that plastic wrapping protects the environment more by saving more cucumbers from spoilage than it harms the environment by the additional use of plastic. If by using the plastic wrap, we reduce cucumber losses at retail even by only 1.1%, its use already has a net environmental benefit. Currently, in the cucumber import supply chain from Spain to Switzerland, the use of plastic wrapping lowers the cucumber losses at retail by an estimated 4.8%; therefore, it makes sense to use it from an environmental perspective. The environmental benefit of food waste reduction due to plastic wrapping the cucumbers was found to be 4.9 times higher than the negative environmental impact due to the packaging itself. Alternative strategies to preserve fresh cucumbers without using plastic wrapping will have to compete with this challenging limit.